Importance of children's fine motor skills in Physical Education classes: A narrative literature review (Research, Society and Development, 2021)
The purpose of the present study was to review the evidence of the contribution of Physical Education in fine motor coordination of Early Childhood Education students. A search was performed throughout Google Scholar database, including articles published between 2010 and March 2021 and using as descriptors: 'motor skills', 'fine motor skills', 'physical education', and 'child physical education'. Original and review research and final project (undergraduate, master and doctor thesis) were included and need to write in Portuguese. Three articles were included, which mostly weave positive information about school Physical Education for the motor skills development. Children motor skills development throughout Physical Education are important until the end of life. Therefore, special attention should be given to these classes, so that these children, in this age group, when they become adults, will not have difficulties in everyday activities, for example, manual activities in their workplace or when doing an ornamentation. It is concluded that children's physical education teachers are the most recommended professionals to develop fine motor skills, with the exception of always seeking knowledge to keep up to date.